Leni Riefenstahl (1935): o cinema documental de propaganda nazista - Quinta Junior, Elbio Roberto (2019)
The exceptionality of "The Triumph of the Will" (1935), as well as its director, Leni Riefenstahl (1902-2003), is remarkable in the specialized literature on the subject of political propaganda in the cinema. Thus, this dissertation aims to examine the specificities of cinema developed by Riefenstahl, through the understanding of his maximal work. To do so, two approaches are necessary. In the first place, the analysis of the Nazi aesthetics through the resurgence of the aura by the Nazi politics aesthetics, made by the German essayist Walter Benjamin. Secondly, the use of the method of "film analysis" for understanding the frames of the film will be analyzed. By doing that, we can see how Leni Riefenstahl built his filmic aesthetic linked to the propaganda project of national socialism. Thus, the dissertation is divided into three moments. We will begin by exposing the peculiarities of Leni Riefenstahl, highlighting their relationship with the Nazi propaganda machine. After that, we argue about "The Triumph of the Will" (1935) as a source, discussing the perspectives for history knowledge, focusing on the genre of propaganda, aesthetics and its relation to the concept of aura, and its relationship with the documentary genre. Finally, we approach the analysis of the aesthetics of the film through its two main characters: the masses and Adolf Hitler.